TINJAUAN HUKUM IZIN MENDIRIKAN BANGUNAN RUMAH TINGGAL DI WILAYAH PESISIR - Wa Ode Zamrud; Muhammad Syarifuddin; Muhammad Ksatria Pansariang (Jurnal Ilmu Hukum Kanturuna Wolio, 2023)
This research focuses on the problem of how to regulate development in the coastal area of Kadolomoko Village, Baubau City and the application of Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands. The results showed that the number of buildings that stood along the coast of Kadolomoko urban village from 2019-2023 was 528 buildings and those that had IMB were 211 buildings, while residential buildings located in the coastal area of Kadolomoko urban village were 266 units that had IMB. (IMB) as many as 150 units or 56.39% and 116 other units or 43.61% do not have a Building Permit (IMB). The lack of public awareness to take care of the Building Permit (IMB) is one of the factors that there are still many who do not have a Building Permit (IMB) and the lack of socialization from the local government.